2019
DOI: 10.5114/aoms.2018.81033
|View full text |Cite
|
Sign up to set email alerts
|

Interventions to increase research publications in graduate medical education trainees: a systematic review

Abstract: IntroductionCompetency-based educational models recommend trainee exposure to research, but the best methods for Graduate Medical Education (GME) programs to accomplish this have not been clarified. The objective of this study was to quantify published interventions to generate resident research and compare effectiveness among those interventions.Material and methodsA systematic review of English-language articles of studies of GME programs was performed, describing resident research interventions and quantify… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
39
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(39 citation statements)
references
References 50 publications
0
39
0
Order By: Relevance
“…Mentorship is an influential factor in a thriving research experience. 10,20,24,25 Prior studies have reported a lack of proper mentoring as a significant barrier for research. 4,8 Residents of TUOMS were less motivated to do research due to 1) mandatory research topics and 2) advisors/ mentors.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Mentorship is an influential factor in a thriving research experience. 10,20,24,25 Prior studies have reported a lack of proper mentoring as a significant barrier for research. 4,8 Residents of TUOMS were less motivated to do research due to 1) mandatory research topics and 2) advisors/ mentors.…”
Section: Discussionmentioning
confidence: 99%
“…Time for research is crucial in clinical residency. 4,8,10,25,26 In the TUOMS research program, a protected one month period during the first year of residency was allocated to proposal writing, but program directors did not consider a similar protected time for research execution. Although one month of protected time helped residents complete proposals, it caused understaffed wards, scheduling difficulties, and residents missing some clinical experience.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations